Bilinguismo: discursos de professores em área de fronteira, Bonfim-RR - Cunha, Patrícia Socorro da Costa (2012)
The present study sought to analyze the speech teachers of Portuguese language of the municipality of Bonfim, on the border between Brazil, Guyana to check how these professionals deal with the bilingualism of your students in their teaching practices. This qualitative ethnographic research sought to understand how nature in a region where there is high prevalence of linguistic and cultural diversity permeate the questions concerning linguistic plurality existing there, and know how is ingrained in the discursive practices of the teachers the idea of cultural hegemony, monocultural curriculum and monolinguistico. To answer this question as theoretical and methodological contribution to discourse analysis is the construction of another look on language practices and resizing the object of analysis: the discourse of teachers.Tried to understand the discursive processes on educational practices of these teachers looking to analyze their ideological, social and discursive formation within a context of border. These professionals work in a bilingual reality where most of his students come from Lethem or indigenous communities, these being English speakers or an Indian language Macuxi indigenous, Wapixana and/or in addition to Portuguese. As a result of this study, it was found that in this nvironment, the teacher says not ready to cope with such reality, since there are educational programs in the municipality that endear this linguistic diversity and so little he says it is ready to act in this context as a result of higher institutions prepare it properly to deal with such a situation.